METODE PEMBELAJARAN BCCT (BEYOND CENTERS AND CIRCLE TIME) UNTUK PERKEMBANGAN NILAI AGAMA DAN MORAL ANAK USIA DINI - Nurul Hayati; Siti Nurjanah (Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
Abstract: The purpose of this study was to determine the development of aspects of child development through the central learning method. With the formulation of the research problem, How is the implementation of BCCT learning in Early Childhood Development at RA Muslimat NU 05 Jenu, what are the aspects of early childhood development in the implementation of learning with the BCCT approach at RA Muslimat NU 05 Jenu, How is the effectiveness of the implementation of the BBCT learning method in child development Early Age at RA Muslimat NU 05 Jenu?. This study uses a qualitative method, with a descriptive type of approach. With data sources from Principals, Teachers, and Students of group B RA Muslimat NU 05 Jenu, the results of this study are RA Muslimat NU 05 Jenu in the BCCT learning method at the imtaq center, with the learning stages: the footing of the playing environment, the footing before playing, the footing during playing, and the footing after playing. The self-development activities selected and implemented by RA Muslimat NU 05 in the Aspects of the Development of Religious and Moral Values ​​for children are knowing worship to Allah SWT, in the form of activities carried out by reading and writing the Qur'an, memorizing short letters, introducing the story of the prophet, memorizing Asmaul Husna, memorizing and praying the intentions of worship, as well as the practice of worship. Based on the recapitulation of the assessment, it shows that the average development of religious and moral values ​​in groups B1 and B2 gets an assessment of developing according to expectations (BSH). So it can be concluded that the BCCT method is effective in supporting the development of early childhood religious and moral values.